Steppingstones to Appreciating the Importance of Play in the Creative Act (LEARNing Landscapes, 2012)
This paper documents how the literature on creativity has inspired a professor to live and teach creatively. Through a weaving of stories with the literature, the paper demonstrates that praxis is achievable and can be fun! It is hoped that the stories will inspire the readers to take risks and become more playful and creative in all aspects of their lives.
Keywords: creativity; praxis; story; play